Manno-oligosaccharides from copra meal: Optimization of its enzymatic production and evaluation its potential as prebiotic. (May 2022) - Intaratrakul, Kwankanit; Nitisinprasert, Sunee; Nguyen, Thu-Ha; Haltrich, Dietmar; Keawsompong, Suttipun
Abstract: A recombinant β-mannanase from Bacillus circulans NT 6.7 was used for the production of manno-oligosaccharides (MOS) from copra meal. The optimum hydrolysis condition was determined by response surface methodology. A maximum MOS concentration of 1.96 mg/ml was obtained when employing 9 mg of defatted copra meal and 9 U of recombinant β-mannanase per ml, incubated at 50 °C for 15.5 h. Hydrolysis products in copra meal hydrolysate (CMH-R) consisted of 0.80, 0.70, 0.46 and 0.01 mg/ml of mannotetraose, mannotriose, mannobiose and mannose, respectively. CMH-R was highly resistant to simulated gastrointestinal condition, with 3.52% and 6.59% hydrolyzed under in vitro simulated stomach and small intestine condition, respectively. Moreover, CMH-R showed potential to promote the growth of Lactobacillus reuteri AC5, Lactobacillus johnsonii KUNN 19-2, Weisella confusa JCM 1093, Bifidobacterium bifidum TISTR 2129, and Bifidobacterium animalis subsp. animalis TISTR 2194, as well as Escherichia coli KUB-E010, Salmonella Enteritidis KUB-S003, and Staphylococcus aureus TISTR 029 similar to Fructooligosaccharide (FOS) with a specific growth rate 0.24–1.41 h −1 . Conversely, CMH-R did not enhance the growth of the pathogenic bacterium S. dysenteriae DMST 1511. Hence, copra meal hydrolysate containing manno-oligosaccharides prepared by recombinant β-mannanase shows a potential to be used as a prebiotic which can be employed in both food and feed applications.